2019
DOI: 10.3390/buildings9080185
|View full text |Cite
|
Sign up to set email alerts
|

A Solar Thermal Application for Mongolian Detached Houses: An Energy, Environmental, and Economic Analysis Based on Dynamic Simulations

Abstract: Ulaanbaatar (Mongolia) is the coldest capital city in the world with approximately 98% of its heating demand satisfied by means of coal-burning stoves. This leads to enormous air pollutant emissions, with Ulaanbaatar being one of the top five most polluted cities in the world. In this study, an innovative solar hybrid heating system for the Mongolian scenario was used, which was based on the operation of a solar field composed of four series-connected evacuated tube heat pipe collectors, coupled with a thermal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…Houses 1, 2, 3 and 4&5, is 112 kWh/m 2 /yr, which is about 71% lower than the energy consumption for reference non-apartment buildings (around 395 kWh/m 2 /yr). The results reported here compare reasonably well with other studies [16]; which reported 8.97-9.69 MWh (8 months, Oct-May) as the simulated thermal energy supplied to a case study house of 48 m 2 , leading to an EUI of 187-202 kWh/m 2 /yr. When compared to a target set by foreign investors, like Asia Development Bank (ADB), of 150 kWh/m 2 /yr, the CALE development is 23% more energy efficient than the target value.…”
Section: Findings From Measurement and Verificationsupporting
confidence: 90%
See 1 more Smart Citation
“…Houses 1, 2, 3 and 4&5, is 112 kWh/m 2 /yr, which is about 71% lower than the energy consumption for reference non-apartment buildings (around 395 kWh/m 2 /yr). The results reported here compare reasonably well with other studies [16]; which reported 8.97-9.69 MWh (8 months, Oct-May) as the simulated thermal energy supplied to a case study house of 48 m 2 , leading to an EUI of 187-202 kWh/m 2 /yr. When compared to a target set by foreign investors, like Asia Development Bank (ADB), of 150 kWh/m 2 /yr, the CALE development is 23% more energy efficient than the target value.…”
Section: Findings From Measurement and Verificationsupporting
confidence: 90%
“…As the residential buildings in the Ger areas to contribute pollution emissions, it is important to look into the potential for improving housing design and operation. A few studies [13][14][15][16][17][18] in Mongolia and others in the similar climates [19][20][21] have investigated the energy consumption levels and have proposed various improvement strategies. Specifically, for a typical detached house, the average energy use intensity (EUI) is about 400 kWh/m 2 /yr [14] although others have reported lower levels from 315.36 to 210.64 kWh/m 2 /yr [20].…”
Section: Introductionmentioning
confidence: 99%
“…Traditional air conditioning systems primarily rely on artificial cooling and heating sources, such as mechanical refrigeration [3,4], heat pumps [5][6][7], absorption refrigeration [8,9], adsorption refrigeration [10,11], boiler systems [12,13], and solar collectors [14]. While these systems may incorporate renewable energy utilization, they predominantly rely on electrical, thermal, and fuel energy, leading to substantial embodied or life-cycle energy consumption [15].…”
Section: Introductionmentioning
confidence: 99%
“…In terms of natural heating, solar energy and biomass are prominent options [13,14], but each has limitations. For instance, solar energy is subject to meteorological variability and spatial constraints [27].…”
Section: Introductionmentioning
confidence: 99%